Pengaruh Pelatihan Terhadap Kinerja Karyawan (Studi Kasus Pada PT. Borneo Group Kendari) - widayanti, widayanti; sartono, sartono; nurjannah, nurjannah (Universitas Halu Oleo, 2017)
The purpose of this study is to find out whether training has a significant effect on employee performance at PT. Borneo Group Kendari and provide additional references for those who want to conduct research on the Effect of Training on Employee Performance at PT. Borneo Group Kendari. The population in this study were all employees of PT. Borneo Group Kendari with 26 employees. Samples totaling 26 respondents were taken using a simple random sampling technique that is simple random sampling. This study uses simple linear regression analysis. The results of this study indicate that training has a significant effect on employee performance with R square of 0.720 or 72%. This value is included in the category of strong influence. Which means that there is a significant influence between training on employee performance at PT. Borneo Group Kendari. This can be seen from the value of t count 7.848 > t table value 2.063. Thus, that for the value of t count 7.848 > the value of t table 2.063 with a significant level of 0.000 > 0.05, which means that the hypothesis in this study rejects Ho and accepts Ha. Which means that the training hypothesis has a significant influence on the performance of employees at PT. Borneo Group Kendari.